Analisis Nitrogen Dioksida (NO2) terhadap Penurunan Kualitas Udara Ambien: Studi Kasus: Desa Puuruy, Kecamatan Morosi, Kabupaten Konawe, Provinsi Sulawesi Tenggara - Asrudin, Nooraisya; Assiddieq, Moch.; Rosdiana, Rosdiana (Universitas Muhammadiyah Kendari, 2023)
Outdoor air pollution comes from moving sources, namely exhaust fumes from burning vehicles such as motorbikes, cars, buses, trucks. Morosi sub-district is an industrial area inhabited by several mineral refining companies. The company certainly has a lot of human resources, in this case there are many jobs that use vehicles to optimize working time the mobility of workers is one of the contributors to air pollution because of incomplete combustion residue from transportation equipment known as Nitrogen Dioxide (NO2). Efforts to monitor the amount of pollutant (NO2) need to be carried out considering the impacts that will arise in the future. Measurenment of content (NO2) was carried out using measurement procedures referring to SNI 19-71196-2005, using an impinge and a spectrophotometer. This study shows the concentration (NO2) on the Puuruy-Morosi road in the morning reached 85.90 μg/m³,70.30μg/m³ afternoon and 106.20μg/m³ in the afternoon and is still within safe levels for humans because it has not exceeded the air quality standard of 200 μg/m³.